Gene structure and allelic variations of hop (Humulus lupulus L.) bitter acid biosynthesis genes - Hagemann, Michael Helmut; Ute, Ute; Weber, Gerd; Wünsche, Jens Norbert (BrewingScience, 2019)
Hop breeding to date is time-consuming and costly, thus the development of molecular markers that assist the knowledge-driven selection of genotypes from breeding populations is needed. To meet this requirement, modern technologies such as targeted genotyping-by-sequencing are now readily available. Consequently, to initiate the development of markers useful in hop breeding through targeted sequencing approaches, key genes involved in the bitter acid biosynthesis were structurally analyzed. The genes valerophenone synthase (VPS) and the two prenyltransferases 1 (PT1) and 2 (PT2) all had two copies, presumably allelic variations in the genome of the cultivar 'Cascade'. Gene structure analysis revealed two exons in VPS and 10 exons in both PT1 and 2 PT2 with large introns leading to a total length of up to 9 kb and 31 kb, respectively. The long PT2 gene size is due to transposable elements of the Gypsy and Copia family. Real-time quantitative PCR further suggests that, among the three bitter acid genes, the VPS had the statistically most significant association with the genotype typical bitter acid concentration. Moreover, identifying transcription factor binding site (TFBS) modules in all genes reveal promising sequence regions with known regulatory functions of the secondary plant metabolisms. It will be further evaluated whether those TFBS-modules are promising targets for future targeted sequencing approaches.